Experimental studies on evaporation of fuel droplets under forced convection using spray in crossflow methodology. (15th January 2016) - Sinha, Anubhav; Surya Prakash, R.; Madan Mohan, A.; Ravikrishna, R.V.
Abstract: Experimental data on evaporation of droplets of decane, Jet-A1, and Jet-A1 surrogate are generated using a spray in crossflow configuration. The advantage of a crossflow configuration is that it enables us to study droplet evaporation under forced convective conditions involving droplet diameters of size relevant in practical combustors. Specifically, spray from an airblast atomizer is injected into a preheated crossflow of air and the resulting spray is characterized in terms of spray structure along with droplet size and velocity. An existing correlation for the spray trajectory is modified to incorporate the effect of elevated temperature, and is found to be in good agreement with the experimental data. Droplet sizes and velocities are measured at different locations along the crossflow direction to assess droplet evaporation. Specifically, droplets having size less than 25-μm are selected for further analysis since these droplets are observed to exhibit velocities which are aligned with the crossflow. By comparing the droplet diameter profiles at upstream and downstream locations, the evaporation constant k for the d 2 -law is obtained iteratively. To assess the efficacy of the values of k obtained, the calculated droplet size distribution using the proposed k values at the downstream location is compared with the measured droplet size distribution at that location. A reasonably good match is found for all the three liquids confirming the validity of the analysis.